Effects of change in the treatment of exchange differences: accounting and financial impact (Journal of Business, Universidad del Pacífico (Lima, Peru), 2012)
This article is based on a substantial change in the tax treatment of exchange differences of liabilities associated with the purchase of inventory and fixed assets. It aims to determine whether these changes have a significant impact on the interpretation of the main financial indicators of the companies that operate in Peru and whose accounting is based on the guidelines of the tax legislation.To determine if this impact really exist both accounting and tax standards were analyzed and a financial evaluation model was developed. This model allowed examine the variations of selected ratios for the research in response to changing regulations and according to different proposed scenarios. Result of the model concluded that there is a light to medium tendency to distortion of the main financial indicators produced by the change in the tax treatment of the exchange difference.Finally, it is advisable to conduct a meticulous analysis when evaluating entities whose accounting analysis is based on the tax legislation, since with the most recent treatment of exchange differences, the financial position of the company might be misinterpreted if interpreted only the ratios as it could show signs of improvement or deterioration when in fact remains constant.
Keywords: exchange difference